INTERACTIVE LEARNING MULTIMEDIA BASED MICROSOFT EXCEL ON THE TEMPERATURE AND HEAT - Astuti, Irnin Agustina Dwi; Bhakti, Yoga Budi (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2018)
This study aims to do develop interactive learning multimedia based microsoft excel on the temperature and heat. The concept of sciences especially of physics that deals with the formula and application are still difficult to understand by junior high school students. Students only memorization after that, do not apply the equation physics into the concept of about so as to make students quickly forget against an equation physics. Learning use media are still a few in every learning physics because the teacher had not optimized the utilization of media. To solve the problems so created learning innovation in the interactive form of media that can be pulled students in like learn physics by media Microsoft excel. Research methods that were used are the method research and development with the process of 4D (Define, Design, Development, and Dissemination). Research development model 4D performed only reached the stage of development (Development) because the purpose of this research limited only develops and produces a medium learning who deserves to implemented based on the assessment validator. An instrument data collection is sheets of validation to the matter and media experts. Based on the results of validation media experts and the matter obtained the average a score of 3.30 and 3.37 to a category worthy of, so that media learning based Microsoft excel being used as a sciences learning media.